Chronic postoperative fungal endophthalmitis caused byPenicillium citrinumafter cataract surgery. Issue 9 (September 2016) - Garg, Anurag; Stuart, Alastair; Fajgenbaum, Mark; Laidlaw, David Alistair; Stanford, Miles
Abstract : N/A: An 85‐year‐old man developed chronic postoperative endophthalmitis after complicated cataract surgery. Visual acuity in the affected eye was hand movements. Slitlamp biomicroscopy showed a hypopyon, superonasal iris nodule, and marked vitritis. An anterior chamber washout, iris biopsy, and intravitreal amphotericin injection were performed. Panfungal polymerase chain reaction of anterior chamber and vitreous samples were positive for Penicillium citrinum . The iris biopsy showed hyphae on Grocott staining. Despite treatment, the patient's acuity deteriorated to light perception and he developed severe intractable pain requiring evisceration. Histological analysis showed diffuse infiltration of hyphae. Penicillium species are fungal organisms that are ubiquitous in the environment and can cause chronic endophthalmitis. They are commonly dismissed as culture contaminants. True infection is confirmed by histological demonstration of fungal invasion. Diagnosis can be aided by iris biopsy if iris nodules are present. Polymerase chain reaction testing was beneficial in identifying the causative organism and should be considered early in endophthalmitis cases. Despite intravitreal and systemic antifungal treatment, the visual prognosis for this condition is variable. Financial Disclosure : None of the authors has a financial or proprietary interest in any material or method mentioned.